Care of patients with colostomies: Challenges and perspectives of the health professional (Research, Society and Development, 2022)
Introduction: The exteriorization of a part of the organ from the surgical procedure is defined as an ostomy. When dealing with the large intestine, it is called colostomy, a procedure performed to eliminate food bolus that will become feces. A collection bag is adapted to this specific ostomy where, in contact with the abdomen, it will carry out the drainage of the effluents. This procedure can be temporary or permanent depending on the patient's condition. Objective: The present work aims to present the care of patients with colostomy, as well as the challenges and perspectives of health professionals. Methodology: This is a systematic literature review study, where the initial search via the Virtual Health Library (VHL) resulted in 30 results, comprising 15 articles for the study. Results and Discussion: The difficulties encountered by health professionals with colostomized patients include the lack of adherence to the new routine, causing injury and consequently more painful adaptation, as well as psychological factors that prevent successful adherence, leading to to challenges for these professionals, being essential the multiprofessional and integral work with the patient. Final considerations: Restoring the patient's well-being, ensuring their quality of life will be what professionals expect. The importance of a humanized and individualized approach to colostomized patients is highlighted, making care unique and differentiated.